Study on the dynamic magnetic behaviors in a ferrimagnetic mixed spin Ising ladder-type graphene nanoribbon. (3rd May 2021) - Gao, Zhong-yue; Lv, Dan; Wang, Wei; Yu, Jie
Abstract: In this work, we discussed the dynamic magnetic behaviors of a ferrimagnetic mixed spin-1 and spin-3/2 Ising ladder-type graphene nanoribbon in a time-dependent magnetic field by utilizing Monte Carlo simulation. The influence of exchange couplings, crystal-field, time-dependent oscillating magnetic field as well as temperature on the magnetic properties and hysteresis behaviors of the system was studied in detail. Various curves of the dynamic order parameter, susceptibility and internal energy of the system and hysteresis loops were obtained for different Hamiltonian parameters. What is striking is that the system may display double-loop hysteresis behavior under certain parameters. Graphical abstract: An Ising model of ladder-type graphene nanoribbon is proposed and multiple saturation values of the total dynamic order parameter are found in the system. Image 1 Highlights: F0B2 A ferrimagnetic mixed spin Ising ladder-type graphene nanoribbon was studied under a time-dependent magnetic field. F0B2 The dynamic order parameter, the susceptibility and the internal energy were discussed by Monte Carlo simulation. F0B2 The phase diagrams and the double-loop hysteresis behavior were obtained.